2015
DOI: 10.1088/0268-1242/30/3/035023
|View full text |Cite
|
Sign up to set email alerts
|

Scavenging effect on plasma oxidized Gd2O3grown by high pressure sputtering on Si and InP substrates

Abstract: In this work, we analyze the scavenging effect of titanium gates on metal-insulatorsemiconductor capacitors composed of gadolinium oxide as dielectric material deposited on Si and InP substrates. The Gd 2 O 3 film was grown by high pressure sputtering from a metallic target followed by an in situ plasma oxidation. The thickness of the Ti film was varied between 2.5 and 17 nm and was capped with a Pt layer. For the devices grown on Si, a layer of 5 nm of Ti decreases the capacitance equivalent thickness from 2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2017
2017

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…After Ti evaporation, a FGA at 300 °C for 20 min performed to improve the backside metallic contacts and produce scavenging. The scavenging electrode and FGA conditions used where the best ones that were optimized in [27] for 4 nm of Gd 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After Ti evaporation, a FGA at 300 °C for 20 min performed to improve the backside metallic contacts and produce scavenging. The scavenging electrode and FGA conditions used where the best ones that were optimized in [27] for 4 nm of Gd 2 O 3 .…”
Section: Resultsmentioning
confidence: 99%
“…This process holds the promise of extremely low EOTs by controlling the interfacial layer thickness and oxygen content. In [27,28] we showed that this scavenging also works on Gd 2 O 3 films deposited by HPS on Si and even on InP. In this work we will use Ti/Pt gate electrodes to study the possibility of scavenge the interface of HPS deposited Gd 2−x Sc x O 3 .…”
Section: Introductionmentioning
confidence: 97%
“…More recently, HPS has been used to deposit high permittivity dielectrics such as HfO 2 and Gd 2 O 3 [10][11][12]. However, high pressure plasmas are known to be a propitious environment for the formation of dust particles [13] that could be related with the presence of undesirable species in the plasma.…”
Section: Introductionmentioning
confidence: 99%